PENGEMBANGAN BUDAYA ORGANISASI DALAM LEMBAGA PENDIDIKAN - Muhammad Hidayat Yusuf (Universitas Islam Nahdlatul Ulama Jepara, 2017)
Organizational culture is a unity of values, systems, adopted and used as a common guideline of both individuals and groups in organizations or aninstitution.The organization or group will experience progress anddevelopment, if the organizational culture within an organization and theinstitution is organized and run well.In this paper, the authors find stages in the concept of organizational culture development and relevant to beapplied in Islamic educational institutions, that is: Organizational cultureconcept, function and development of organizational culture, organizationalculture type consist of open and participative culture; and closed andautocratic culture,The formation of organizational culture, the strategy ofstrengthening the organizational culture consists of (Mechanical solidarityand organic solidarity), as well as strategies in developing organizational culture. This, it is appropriate to be the focus of reference for Islamic educational institutions, especially in achieving the desired goals. Budaya organisasi merupakan satu kesatuan nilai-nilai, sistem, yang dianut dan dijadikan pedoman bersama baik individu maupun kelompok pada organisasi atau suatu lembaga. Organisasi atau kelompok akan mengalami perkembangan dan kemajuan, jika budaya organisasi dalam sebuah organisasi dan lembaga tersebut terorganisir serta berjalan dengan baik. Dalam tulisan ini, penulis menemukan tahap-tahap dalam konsep pengembangan budaya organisasi dan relevan untuk diterapkan dalam lembaga pendidikan Islam, yaitu: konsep budaya organisasi, fungsi dan pengembangan budaya organisasi, tipe budaya organisasi teridiri dari open and participative culture; danclosed and autocratic culture, pembentukan budaya organisasi, strategi memperkuat budaya organisasi terdiri dari (solidaritas mekanik dan solidaritas organik), serta strategi dalam mengembangkan budaya organisasi. Hal ini, sangat tepat untuk dijadikan fokus acuan bagi lembaga pendidikan islam khususnya dalam mencapai tujuan diinginkan.